2021
DOI: 10.2991/assehr.k.210914.013
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Word Association Test (WAT) Response in Song Study at Students Senior High School 1 Sungai Aur

Abstract: Vocabulary development is a significant purpose in any language teaching. The term that manages vocabularies in the person is named 'mental lexicon'. The mental lexicon describes a dictionary that upgrades every word, meaning, and associate them with another word in the mind. Word Association Test is one measurement to know how depth vocabularies understanding are. It also called Word Affiliation Test and a greatly-renowned research technique in linguistic and psychology research by using word stimulus to acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Although, the complicated and intrinsic nature of mental lexicon may provide relatively abstract features. Nonetheless, WATs provide insight into aspects of information of L2 mental lexicon (Wendari & Zaim, 2021;Xiang & Nam, 2022). Firstly, it has been revealed that L2 learners produce both syntagmatic and paradigmatic responses at higher frequency than the clang words.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the complicated and intrinsic nature of mental lexicon may provide relatively abstract features. Nonetheless, WATs provide insight into aspects of information of L2 mental lexicon (Wendari & Zaim, 2021;Xiang & Nam, 2022). Firstly, it has been revealed that L2 learners produce both syntagmatic and paradigmatic responses at higher frequency than the clang words.…”
Section: Discussionmentioning
confidence: 99%